Solution-processed inorganic bulk nano-heterojunctions and their application to solar cells - Rath, Arup Kumar; Bernechea, Maria; Martinez, Luis; Pelayo Garcia de Arquer, F.; Osmond, Johann; Konstantatos, Gerasimos (Nature Photonics, 2012)
In the last decade, solution-processed quantum dot/nanocrystal solar cells have emerged as a very promising technology for third-generation thin-film photovoltaics because of their low cost and high energy-harnessing potential. Quantum dot solar cell architectures developed to date have relied on the use of bulk-like thin films of colloidal quantum dots. Here, we introduce the bulk nano-heterojunction concept for inorganic solution-processed semiconductors. This platform can be readily implemented by mixing different semiconductor nanocrystals in solution and allows for the development of optoelectronic nanocomposite materials with tailored optoelectronic properties. We present bulk nano-heterojunction solar cells based on n-type Bi2S3 nanocrystals and p-type PbS quantum dots, which demonstrate a more than a threefold improvement in device performance compared to their bilayer analogue, as a result of suppressed recombination.